Molecular Imaging, Pharmacokinetics, and Dosimetry of 111In-AMBA in Human Prostate Tumor-Bearing Mice. (24th May 2011) - Ho, Chung-Li; Liu, I-Hsiang; Wu, Yu-Hsien; Chen, Liang-Cheng; Chen, Chun-Lin; Lee, Wan-Chi; Chuang, Cheng-Hui; Lee, Te-Wei; Lin, Wuu-Jyh; Shen, Lie-Hang; Chang, Chih-Hsien
Abstract : Molecular imaging with promise of personalized medicine can provide patient-specific information noninvasively, thus enabling treatment to be tailored to the specific biological attributes of both the disease and the patient. This study was to investigate the characterization of DO3A-CH2 CO-G-4-aminobenzoyl-Q-W-A-V-G-H-L-M-NH2 (AMBA) in vitro, MicroSPECT/CT imaging, and biological activities of 111 In-AMBA in PC-3 prostate tumor-bearing SCID mice. The uptake of 111 In-AMBA reached highest with 3.87 ± 0.65 % ID/g at 8 h. MicroSPECT/CT imaging studies suggested that the uptake of 111 In-AMBA was clearly visualized between 8 and 48 h postinjection. The distribution half-life ( t 1/2α ) and the elimination half-life ( t 1/2β ) of 111 In-AMBA in mice were 1.53 h and 30.7 h, respectively. The C max ⁡ and AUC of 111 In-AMBA were 7.57% ID/g and 66.39 h ∗ % ID/g, respectively. The effective dose appeared to be 0.11 mSv/MBq -1 . We demonstrated a good uptake of 111 In-AMBA in the GRPR-overexpressed PC-3 tumor-bearing SCID mice. 111 In-AMBA is a safe, potential molecular image-guided diagnostic agent for human GRPR-positive tumors, ranging from simple and straightforward biodistribution studies to improve the efficacy of combined modality anticancer therapy.